2019
DOI: 10.3390/metabo9100199
|View full text |Cite
|
Sign up to set email alerts
|

Steroidomics for the Prevention, Assessment, and Management of Cancers: A Systematic Review and Functional Analysis

Abstract: Steroidomics, an analytical technique for steroid biomarker mining, has received much attention in recent years. This systematic review and functional analysis, following the PRISMA statement, aims to provide a comprehensive review and an appraisal of the developments and fundamental issues in steroid high-throughput analysis, with a focus on cancer research. We also discuss potential pitfalls and proposed recommendations for steroidomics-based clinical research. Forty-five studies met our inclusion criteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…At present, the two most commonly used strategies for metabolomics analysis are untargeted metabolomics and targeted metabolomics[ 21 ]. Untargeted metabolomics, also known as global metabolomics profiling, means that all or most possible metabolites are unbiasedly qualitatively or quantitatively analyzed in given biological samples[ 22 , 23 ].…”
Section: Metabolomics Research Methods and Techniquesmentioning
confidence: 99%
“…At present, the two most commonly used strategies for metabolomics analysis are untargeted metabolomics and targeted metabolomics[ 21 ]. Untargeted metabolomics, also known as global metabolomics profiling, means that all or most possible metabolites are unbiasedly qualitatively or quantitatively analyzed in given biological samples[ 22 , 23 ].…”
Section: Metabolomics Research Methods and Techniquesmentioning
confidence: 99%
“…For other differentially expressed steroids, the most significant of the steroid biomarkers were estradiol, dehydroepiandrosterone and cortisol. Anh et al [38], in their study, pointed to significant changes in steroidogenesis, androgen and estrogen metabolism, and androstenedione metabolism in cancers. Their findings suggest that estradiol, dehydroepiandrosterone, cortisol and estrogen metabolites may be considered as oncosteroids.…”
Section: Steroid Metabolomics In Breast Cancermentioning
confidence: 98%
“…Many studies on steroidomics in clinical diagnosis and doping control have been performed in recent [35][36][37]. Anh et al [38] investigated the role of steroidomics in the prevention, evaluation and treatment of cancer and showed that various types of steroids are significantly associated with common cancers, especially breast, endometrial and prostate cancers.…”
Section: Steroid Metabolomics In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…MS is the primary analytical method on which the emerging omics fields such as proteomics and metabolomics are based. Owing to its potential as a multi-platform analytical method and its diverse applicability from diagnosis and prognosis to the discovery of novel biomarkers for targeted therapies, MS has been routinely applied in omics studies, especially cancer and metabolism-related omics research, for a better insight into human diseases [19][20][21][22][23][24][25][26]. Table 1 displays the main findings of some major studies among the initial achievements of the field.…”
Section: Representative Achievements Of Metabolomics In Public Healthmentioning
confidence: 99%